2016
DOI: 10.3389/fpsyg.2016.00301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hearing Loss and Cognitive Load on Speech Recognition with Competing Talkers

Abstract: Everyday communication frequently comprises situations with more than one talker speaking at a time. These situations are challenging since they pose high attentional and memory demands placing cognitive load on the listener. Hearing impairment additionally exacerbates communication problems under these circumstances. We examined the effects of hearing loss and attention tasks on speech recognition with competing talkers in older adults with and without hearing impairment. We hypothesized that hearing loss wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The significant difference in the strength of the relationships supports the hypothesis that when speech processing in noise is contextually driven, fewer explicit cognitive resources are required to resolve ambiguity than when contextual information is lacking (Moradi et al, 2013 ; Meister et al, 2016 ). Other independent studies suggest that the strength of correlations may vary depending on the type of WMC test (Sörqvist & Rönnberg, 2012; Smith & Pichora-Fuller, 2015 ) and the complexity of sentence materials (Heinrich et al, 2015 ; DeCaro et al, 2016 ).…”
Section: Correlations Among the Level 2 Factorsmentioning
confidence: 56%
“…The significant difference in the strength of the relationships supports the hypothesis that when speech processing in noise is contextually driven, fewer explicit cognitive resources are required to resolve ambiguity than when contextual information is lacking (Moradi et al, 2013 ; Meister et al, 2016 ). Other independent studies suggest that the strength of correlations may vary depending on the type of WMC test (Sörqvist & Rönnberg, 2012; Smith & Pichora-Fuller, 2015 ) and the complexity of sentence materials (Heinrich et al, 2015 ; DeCaro et al, 2016 ).…”
Section: Correlations Among the Level 2 Factorsmentioning
confidence: 56%
“…It is well known that audiometric HL dramatically increases with increasing age 23. SHD is also increased with age as difficulty of speech understanding in adverse listening conditions increases24 due to decreased synaptic loss,25 working memory capacity26 27 or impaired temporal processing 12 28. Our reference group was defined as participants who had both SHD and AHL (concordant HI), so it is highly likely that older participants will have both SHD and AHL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lin et al ( 2011 , 2014 ) found that brain volume and cognitive functioning were associated with the degree of audiometric hearing loss. This suggests that hearing loss can impact speech recognition not only via peripheral auditory deficits but also via reduced cognitive abilities (e.g., Desjardins and Doherty, 2013 ; Smith and Pichora-Fuller, 2015 ; Meister et al, 2016 ). Even if audiometric hearing loss is compensated for through the provision of hearing aids, the effects of cognition on speech recognition can be overshadowed by the effects of audiometric hearing loss (Heinrich et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%